MiR-373 targeting of the Rab22a oncogene suppresses tumor invasion and metastasis in ovarian cancer - Zhang, Yue (Oncotarget, 2014)
Metastasis is major cause of mortality in patients with ovarian cancer. MiR-373 has been shown to play pivotal roles in tumorigenesis and metastasis; however, a role for miR-373 in ovarian cancer has not been investigated. In this study, we show that the miR-373 expression is down-regulated in human epithelial ovarian cancer (EOC) and inversely correlated with clinical stage and histological grade. Ectopic overexpression of miR-373 in human EOC cells suppressed cell invasion in vitro and metastasis in vivo, and the epithelial–mesenchymal transition process. Silencing the expression of miR-373 resulted in an increased migration and invasion of EOC cells. Using integrated bioinformatics analysis, gene expression arrays, and luciferase assay, we identified Rab22a as a direct and functional target of miR-373 in EOC cells. Expression levels of miR-373 were inversely correlated with Rab22a protein levels in human EOC tissues. Rab22a knockdown inhibited invasion and migration of EOC cells, increased E-cadherin expression, and suppressed the expression of N-cadherin. Moreover, overexpression of Rab22a abrogated miR-373-induced invasion and migration of EOC cells. Taken together, these results demonstrate that miR-373 suppresses EOC invasion and metastasis by directly targeting Rab22a gene, a new potential therapeutic target in EOC.